Perfil de segurança dos medicamentos de alta vigilância : uma revisão sistemática de ensaios clínicos randomizados - Menezes, Michelle Santos (2016)
INTRODUCTION. Adverse events have been the focus of studies in various countries, because they occur frequently and increase the morbidity and mortality of patients, constituting a new public health problem, directly impacting on patient safety. High alert medication (HAM) are more predictable to cause significant harm to the patient, even when used as intended. Other authors claim that the damage related to the HAM's lead not only suffering to the patient, but also raise the additional costs associated with care. OBJECTIVE. Evaluate the safety profile of HAM. METHODOLOGY. It was conducted active search for information through COCHRANE databases, LILACS, SciELO, SCOPUS, PubMed / MEDLINE and WEB OF SCIENCE. Then two reviewers independently conducted a preliminary evaluation of relevant titles, abstracts and then finally full text. RESULTS The initial search in the databases identified 1717 articles, which after exclusion of repeated work identified 427 titles, of which 53 are considered potentially relevant abstracts were selected. After evaluation of these, 25 were selected to read the full text. The systematic review evaluated seven articles, which showed that only 11 MAV's were identified in the literature could have serious events. The most frequently cited were warfarin (22.2%), cyclophosphamide (22.2%) and cyclosporine (22.2%).CONCLUSIONS. There were no reported any kind of error in the use of AVM's and particularly serious risks are unlikely because of the risks reported in patients related to drug classes involved. According to the criteria of quality, this revision came just seven articles that address the universe of MAV's, achieving high level of evidence only for six of these, which involved only some drugs: morphine, M6G-glicurônio, haloperidol, promethazine, ivabradine , digoxin, warfarin, ximelagatran, cyclophosphamide, cyclosporin and ATG. The review showed that one of the strategies used to improve security in hospitalized patients and use of AVM's is the creation of these medications protocol, and it is important to evaluate among the classes the drug that causes less damage.